INTEGRASI TEKNOLOGI DALAM PENGAJARAN BAHASA INDONESIA UNTUK ANAK KELAS RENDAH - Rafli, Muhammad Febri; Pangabean, Dewi Sartika (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
The importance of using technology in the context of education is growing along with the progress of the times. One aspect that requires special attention is teaching Indonesian to lower grade children. This study aims to explore and analyze the integration of technology in learning Indonesian, with a focus on the development of children's language skills and learning motivation. The author, Khairunnisa, a student of the Elementary School Teacher Education Study Program (PGSD) at Batutta University, uses a qualitative research method with a case study approach. The qualitative approach was chosen to provide an in-depth understanding of the use of technology in teaching Indonesian to lower grade children. Case studies are used to describe specific learning contexts and to explore unique experiences of interactions between teachers, students, and technology in Indonesian classes. The literature review discusses the role of technology in education, the urgency of teaching Indonesian to lower grade children, and models of technology integration in learning. This literature is the basis for understanding the theoretical and contextual foundations of the study. The research method involves classroom observation, interviews with Indonesian teachers, and analysis of children's language test results. Classroom observations provide a direct picture of how technology is integrated into the daily learning process. In-depth teacher interviews are used to obtain their views and experiences related to the use of technology in teaching Indonesian. Analysis of children's language test results was used to measure the impact of technology use on the development of their language skills. The findings of this study include effective technology integration strategies, the impact of technology use on language skills, and children's learning motivation through the use of technology. Effective strategies include the use of interactive learning software, educational applications, and relevant online resources. The impact of technology use is seen in the improvement of children's language skills, especially in the aspects of listening, speaking, reading, and writing skills. In addition, the use of technology also increases children's learning motivation, arouses their interest in the subject matter, and creates a more enjoyable learning atmosphere. The discussion of the research results is placed within the framework of the theory of learning Indonesian for lower-grade children. The implications of these findings for improving the quality of teaching in the PGSD Study Program are explained in detail. The conclusions of the study emphasize the importance of technology integration in teaching Indonesian to meet the demands of the times and prepare children to face global challenges. This journal makes a significant contribution to our understanding of the importance of technology integration in the context of teaching Indonesian to lower-grade children. The practical implications of these findings can be used as a basis for developing more effective curriculum and teaching strategies at the PGSD level.